Pengaruh Motivasi Diri, Lingkungan Keluarga, Pertimbangan Pasar Kerja Dan Penghargaan Finansial Terhadap Minat Menjadi Akuntan Profesional: Studi Empiris Pada Mahasiswa Program Studi Akuntansi Universitas AKI Di Semarang - Sri Kawuri; Sukristanta Sukristanta (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
Professional accountant profession is one of the professions that is considered promising, especially by students majoring in Accounting in their studies. There are several factors that influence this interest, including self-motivation, family environment, job market considerations and financial rewards as variables that affect the intention as the professional accountant. This research was conducted on 102 students of the AKI University Accounting Study Program in Semarang. The analysis method were used multiple regression analysis. The results showed that self-motivation, family environment, job market considerations and financial rewards had a positive and significant effect on the intention as the professional accountant.